An Algebraic Aid in Teaching the Differences Between Direct Costing and Full-Absorption Costing Methods. - DeCoster, Don T.; Ramanathan, Kavasseri V. (The Accounting Review, 1973)
The article discusses the use of a numerical problem calling for comparative income statements and the teaching of the conceptual difference between direct and absorption costing models. It is often difficult to find a parsimonious way to introduce the student to the conceptual differences between direct and absorption costing. This is particularly true when the student is introduced first to absorption costing where the fixed overhead rate and the variable overhead rate are subsumed in the total overhead rate. Where the students have been accustomed to thinking symbolically, it is much easier to introduce these two models simultaneously. Mathematically the two components in the volume variance are not independent, and the fact that the dollar measure of the volume variance is meaningless without further analysis is clearly highlighted. This approach has been useful where the students have had a minimal introduction to algebraic logic. Its sole purpose is to clarify two relatively simple models and their impacts upon income.